PI3K‐dependent multiple myeloma cell survival is mediated by the PIK3CA isoform. (26th April 2014) - Hofmann, Claudia; Stühmer, Thorsten; Schmiedl, Nadine; Wetzker, Reinhard; Mottok, Anja; Rosenwald, Andreas; Langer, Christian; Zovko, Josip; Chatterjee, Manik; Einsele, Hermann; Bargou, Ralf C.; Steinbrunn, Torsten
Summary Constitutive phosphatidylinositide 3‐kinase (PI3K) signalling has been implicated in multiple myeloma (MM) pathophysiology and is regarded as an actionable target for pharmacological intervention. Isoform‐specific PI3K inhibition may offer the most focused treatment approach and could result in greater clinical efficacy and reduced side effects. We therefore performed isoform‐specific knockdown of PIK3CA, PIK3CB, PIK3CD, and PIK3CG to analyse their individual contributions to MM cell survival and downstream signalling. In addition, we tested the effectivity of the novel PI3K isoform‐specific inhibitors BYL‐719 (PIK3CA), TGX‐221 (PIK3CB), CAL‐101 (PIK3CD), and CAY10505 (PIK3CG). We found the PIK3CA isoform to be of paramount importance for constitutive Akt activity in MM cells, and – in contrast to inhibition of other class I isoforms – only the blockade of PIK3CA was sufficient to induce cell death in a sizeable subgroup of MM samples. Furthermore, pharmacological PIK3CA inhibition in combination treatments of BYL‐719 and established anti‐myeloma agents resulted in strongly enhanced MM cell death. Our data thus clearly indicate therapeutic potential of PIK3CA inhibitors and support their clinical evaluation in multiple myeloma.